Community-based HIV prevalence in KwaZulu-Natal, South Africa: results of a cross-sectional household survey. Issue 8 (August 2018) - Kharsany, Ayesha B M; Cawood, Cherie; Khanyile, David; Lewis, Lara; Grobler, Anneke; Puren, Adrian; Govender, Kaymarlin; George, Gavin; Beckett, Sean; Samsunder, Natasha; Madurai, Savathree; Toledo, Carlos; et al.
Summary: Background: In high HIV burden settings, maximising the coverage of prevention strategies is crucial to achieving epidemic control. However, little is known about the reach and effect of these strategies in some communities. Methods: We did a cross-sectional community survey in the adjacent Greater Edendale and Vulindlela areas in the uMgungundlovu district, KwaZulu-Natal, South Africa. Using a multistage cluster sampling method, we randomly selected enumeration areas, households, and individuals. One household member (aged 15–49 years) selected at random was invited for survey participation. After obtaining consent, questionnaires were administered to obtain sociodemographic, psychosocial, and behavioural information, and exposure to HIV prevention and treatment programmes. Clinical samples were collected for laboratory measurements. Statistical analyses were done accounting for multilevel sampling and weighted to represent the population. A multivariable logistic regression model assessed factors associated with HIV infection. Findings: Between June 11, 2014, and June 22, 2015, we enrolled 9812 individuals. The population-weighted HIV prevalence was 36·3% (95% CI 34·8–37·8, 3969 of 9812); 44·1% (42·3–45·9, 2955 of 6265) in women and 28·0% (25·9–30·1, 1014 of 3547) in men (p<0·0001). HIV prevalence in women aged 15–24 years was 22·3% (20·2–24·4, 567 of 2224) compared with 7·6% (6·0–9·3, 124 of 1472; p<0·0001) in men of the same age. Prevalence peaked at 66·4% (61·7–71·2, 517 of 760) in women aged 35–39 years and 59·6% (53·0–66·3, 183 of 320) in men aged 40–44 years. Consistent condom use in the last 12 months was 26·5% (24·1–28·8, 593 of 2356) in men and 22·7% (20·9–24·4, 994 of 4350) in women (p=0·0033); 35·7% (33·4–37·9, 1695 of 5447) of women's male partners and 31·9% (29·5–34·3, 1102 of 3547) of men were medically circumcised (p<0·0001), and 45·6% (42·9–48·2, 1251 of 2955) of women and 36·7% (32·3–41·2, 341 of 1014) of men reported antiretroviral therapy (ART) use (p=0·0003). HIV viral suppression was achieved in 54·8% (52·0–57·5, 1574 of 2955) of women and 41·9% (37·1–46·7, 401 of 1014) of men (p<0·0001), and 87·2% (84·6–89·8, 1086 of 1251) of women and 83·9% (78·5–89·3, 284 of 341; p=0·3670) of men on ART. Age, incomplete secondary schooling, being single, having more than one lifetime sex partner (women), sexually transmitted infections, and not being medically circumcised were associated with HIV-positive status. Interpretation: The HIV burden in specific age groups, the suboptimal differential coverage, and uptake of HIV prevention strategies justifies a location-based approach to surveillance with finer disaggregation by age and sex. Intensified and customised approaches to seek, identify, and link individuals to HIV services are crucial to achieving epidemic control in this community. Funding: The President's Emergency Plan for AIDS Relief through the Centers for Disease Control and Prevention.